Automatic Determination of Neovascularization Area with Adaptive Histogram Equalization - Catalbas, Mehmet Cem; Issever, Didem; Gulten, Arif (Ieee, 2015)
In this work, the determination of corneal neovascularization ratio is examined in the light of image processing techniques. The adaptive histogram equalization method for used to increase the success of retinal blood vessel areas on preprocess. Also, various morphological operations were performed on the cornea image to improve the performance of the blood vessel patterns determination.
Medical Technologies National Conference (TIPTEKNO) -- OCT 15-18, 2015 -- Bodrum, TURKEY
Keywords: Biomedical image processing; Hough transform; image erosion; image dilation; adaptive histogram equalization; vessel detection; feature extraction